2001
DOI: 10.1095/biolreprod65.2.358
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of MEK-Mitogen-Activated Protein Kinase Pathway in Follicle-Stimulating Hormone-Induced but Not Spontaneous Meiotic Resumption of Mouse Oocytes1

Abstract: Mitogen-activated protein (MAP) kinase has been reported to be activated during oocyte meiotic maturation in a variety of mammalian species. However, the mechanism(s) responsible for MAP kinase activation and the consequence of its premature activation during gonadotropin-induced oocyte meiotic resumption have not been examined. The present experiments were conducted to investigate the possible role of MAP kinase in FSH-induced and spontaneous oocyte meiotic resumption in the mouse. MAP kinase kinase (MAPKK, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 54 publications
2
44
0
1
Order By: Relevance
“…46 Protein samples were seperated in discontinuous Bis-Tris Gels (Invitrogen NP0316) followed by blotting onto PVDF membrane (Millipore IPVH00010). The following primary antibodies were used for western blot: a-tubulin (Sigma T5168), 1:10,000; b-actin (Sigma A5441), 1:10,000; PP2Ac (CST 2038), 1:1,000; securin (Abcam, ab3305).…”
Section: Protein Sample Preparation and Western Blottingmentioning
confidence: 99%
“…46 Protein samples were seperated in discontinuous Bis-Tris Gels (Invitrogen NP0316) followed by blotting onto PVDF membrane (Millipore IPVH00010). The following primary antibodies were used for western blot: a-tubulin (Sigma T5168), 1:10,000; b-actin (Sigma A5441), 1:10,000; PP2Ac (CST 2038), 1:1,000; securin (Abcam, ab3305).…”
Section: Protein Sample Preparation and Western Blottingmentioning
confidence: 99%
“…In order to study the effects of MEK/ERK/p90 rsk cascade inhibition on meiotic maturation of mouse oocytes, cumulus-free and GV intact oocytes were incubated in M2 medium containing 1.5 M U0126 [19]. The culture medium containing U0126 was renewed every 12 h to prevent the possible degradation of U0126.…”
Section: Division Patterns and Activity Of Map Kinase And P90 Rsk In mentioning
confidence: 99%
“…When incubated in a medium with U0126, part of porcine oocytes completed the second meiotic division and entered into interphase [18]. In cumulus-enclosed mouse oocytes, U0126 produced a dose-dependent inhibitory effect on FSH-induced meiotic resumption [19].…”
Section: Introductionmentioning
confidence: 99%
“…4C ) ( P < 0.05). Previous reports showed that mice CEOs started to resume meiosis in 8 h if they were treated with FSH existing media ( 36 ). Therefore, we detected the protein expression of CYP51 at 8 h after FSH treatment and found that siRNAs decreased CYP51 protein levels within the 8 h culture period ( Fig.…”
Section: Rnai Silenced Cyp51 Gene Expression In In Vitro Cultured Feomentioning
confidence: 69%